2009
DOI: 10.3917/eufor.351.0067
|View full text |Cite
|
Sign up to set email alerts
|

What have we learned about prices and inflation in 10 years of monetary union?

Abstract: Distribution électronique Cairn.info pour Centre international de formation européenne. © Centre international de formation européenne. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Aucremanne at al. [2] showed that the establishment of EMU and the single monetary policy influenced inflation dynamics in member countries. ECB brought unprecedented price stability in Eurozone, and to some extend even the decrease in inflation persistence, thanks to monetary policy focused on price stability and thus lower inflation expectations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aucremanne at al. [2] showed that the establishment of EMU and the single monetary policy influenced inflation dynamics in member countries. ECB brought unprecedented price stability in Eurozone, and to some extend even the decrease in inflation persistence, thanks to monetary policy focused on price stability and thus lower inflation expectations.…”
Section: Literature Reviewmentioning
confidence: 99%